Isolasi dan Uji Bioaktivitas Senyawa Metabolit Sekunder Ekstrak N-Heksan Daun Pare (Momordica charantia L.) - Muharram, . (Fakultas MIPA UNM, 2010)
Bittermelon (Momordica charantia L.) is a bioactivity plant that used as a medicine traditional. The purpose of this research is to isolate the bioactivity secondary metabolites of n-hexane extract from the bittermelon leaves and bioassay toward larval shrimp A. salina. Isolation of the secondary metabolites including extraction, fractionation, purification, and identification. Bioassay was conducted to the extract and to mixed fractions (fraction A – G) the results of column chromatography. The results of research showed that the extracts and fractions from bittermelon leaves was toxic to A. salina. The LC50 from extracts bittermelon leaves was 91, 84 ppm. The LC50 for the fractions A and B (steroid) were 38,26 ppm and 85,90 ppm, the fractions C – G (terpenoid) were 94,45 ppm; 79,56 ppm; 92,53 ppm; 70,41 ppm; and 92,69 ppm, the most toxic fractions was fraction of A. From the C-fraction as a green coulor was obtained a crystal and needle-shaped. After recystalization with n-hexane and ethylacetat was obtained a pure compound that positive to terpenoids with Liebermann-Burchard reagents.